2007
DOI: 10.1016/j.paid.2006.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of expectancies for post-surgical pain and fatigue in breast cancer surgical patients

Abstract: Expectancies for post-surgical pain and fatigue have previously been found to predict pain and fatigue among breast cancer surgery patients. However, the study of predictors of these expectancies has been neglected. The present study was designed to investigate predictors of expectancies for postsurgical pain and fatigue among breast cancer surgery patients.Four hundred and eighteen women (M = 48.3 years, SD = 13.66 years) scheduled to undergo excisional breast biopsy or lumpectomy completed questionnaires ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 33 publications
1
36
1
Order By: Relevance
“…These findings suggest that perceived pain and other adverse symptoms are not related to the extent of BCA surgery, which is consistent with previous findings (Caffo et al, 2003; Montazeri et al, 2008). Pre-surgical distress and expectancies of pain and fatigue have been found to predict post-surgical pain and fatigue in women with BCA (Schnur et al, 2007). While the small sample sizes of each surgical subgroup likely affected the ability to detect significant differences among other cytokine levels, these preliminary results provide some support of altered pro- and anti-inflammatory cytokines levels at one month post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that perceived pain and other adverse symptoms are not related to the extent of BCA surgery, which is consistent with previous findings (Caffo et al, 2003; Montazeri et al, 2008). Pre-surgical distress and expectancies of pain and fatigue have been found to predict post-surgical pain and fatigue in women with BCA (Schnur et al, 2007). While the small sample sizes of each surgical subgroup likely affected the ability to detect significant differences among other cytokine levels, these preliminary results provide some support of altered pro- and anti-inflammatory cytokines levels at one month post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients' expectations for postsurgical pain and fatigue after breast excisional biopsy or lumpectomy can be affected by acute presurgical distress, previous experience with same surgical procedure, anxiety, presurgical pain and fatigue, and age. 15 Consideration of these factors in analysis of pain also may help to identify highrisk patients.…”
Section: And Nationalmentioning
confidence: 99%
“…This finding may be related with educated women, whom may have much information about breast cancer and its treatment. State anxiety contributes to trait anxiety and increased levels of anxiety result in elevated levels of pain (Cauma et al, 2001;Katz et al, 2005;Schnur et al, 2007). In the study, there is very slightly correlation between trait anxiety and total analgesic consumption.…”
Section: Discussionmentioning
confidence: 72%
“…Vaughn et al (2007) reviewed literature and they found a positive correlation between preoperative anxiety and postoperative pain. Schnur et al (2007) have reported that patients who experience severe psychological distress prior to surgery are expected to have more postoperative pain. Similarly, Katz et al (2005) have shown that preoperative anxiety contributes to acute pain following surgery.…”
Section: Discussionmentioning
confidence: 99%